Pelatihan Pemasaran dan Pendampingan Legalitas Produk UMKM - Thalib, Tasha Tsania; Trianita, Elok; Nafis, M. Jauhar; Alfaiq, Muhammad Nurus Sobah; Fawa’id, Muhamad Wildan (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Pandantoyo Village is a village that has MSME products for both individuals and groups, which are managed by the village. However, what is very unfortunate for society is that product marketing is less than optimal, and many products have not received halal legality. Based on this, our team held training related to the marketing and legality of MSME products with the aim of providing the public with innovations regarding how to market products in the digital era and raising awareness about the importance of managing business legality in accordance with government recommendations. The training, which was attended by around 35 people, went smoothly, and the output obtained from the training was that people made more use of technology to market products, and several MSMEs had applied for Business Identification Numbers (NIB), which could later be used to register their businesses to obtain halal certification. The impact that can be felt by business actors from this activity is that the products marketed receive permits and are assessed as halal in accordance with the provisions imposed by the government and the Indonesian Ministry of Religion.